Social Media Marketing as a Strategy for New Business De-velopment in Indonesia: A Narrative Review - Shapely Ambalao; Kenneth Sahetapy (STIE Amkop Makassar, 2026)
Purpose: This review synthesizes empirical evidence from Indonesia on how social media marketing supports new business development and identifies the capabilities and conditions that convert platform use into performance. Research Method: A narrative review covered 13 peer-reviewed empirical studies published from January 2019 to 16 June 2026. Eligible studies used primary data from Indonesian MSMEs or small businesses and linked social media adoption, use, or marketing with organizational capabilities, marketing outcomes, or business performance. Study characteristics and findings were coded in a structured matrix and synthesized thematically and comparatively. Results and Discussion: Social media consistently expands market reach, customer interaction, and low-cost promotion, but adoption alone does not ensure performance. Relational, informational, marketing, and innovation capabilities explain stronger sales, engagement, and business outcomes. Entrepreneurial orientation, owner support, platform fit, organizational readiness, and institutional pressure shape adoption, while effects differ across sectors and platforms. Implications: New businesses should manage social media as a staged market-learning system linked to customer records and transactions. Support programs should emphasize strategic content, analytics, customer management, and platform-specific skills. Originality: The review offers an Indonesia-specific synthesis and a four-stage framework connecting social media activity with discovery, validation, conversion, retention, and learning.